An analytical method for the simultaneous quantification of 30 bioactive compounds in spent coffee ground by HPLC‐MS/MS. (5th May 2020) - Angeloni, Simone; Nzekoue, Franks Kamgang; Navarini, Luciano; Sagratini, Gianni; Torregiani, Elisabetta; Vittori, Sauro; Caprioli, Giovanni
Abstract: Spent coffee ground (SCG) is the remaining residue produced after extraction of coffee, and it is considered a source of unextracted bioactive compounds. For this, in the latest years, the attention has been focused to innovative reuses that can exploit the potentiality of SCG. Unfortunately, the content of bioactive compounds has not been thoroughly studied yet, and the major of publication has investigated the caffeine and chlorogenic acids levels, total polyphenol contents, and total flavonoid content. Hence, these approaches have determined only an estimation of flavonoids and polyphenols content and lack on single polyphenols investigation. Therefore, the objective of the current work was to provide a deep characterization of bioactive compounds in SCG. For this purpose, a new analytical method for the quantification of 30 molecules, including caffeine, chlorogenic acids, phenolic acids, flavonoids, and secoiridoids, has been developed using high‐performance liquid chromatography tandem mass spectrometry. Moreover, several extraction procedures, that is, liquid–solid extraction assisted and not by ultrasounds, testing diverse solvents, were evaluated. Liquid–solid extraction assisted by sonication, with water/ethanol (30/70, v/v), resulted the best in terms of total bioactive compounds, and, once validated, the new analytical method was applied to five different espresso SCG samples. Data showed that caffeine (means: 1193.886 ± 57.307 mg kg −1 ) and chlorogenic acids (means of total CQAs: 1705.656 ± 88.694 mg kg −1 ) were the most abundant compounds in all SCG samples followed by phenolic acids such as caffeic, ferulic, gallic, p ‐coumaric, syringic, trans ‐cinnamic, and vanillic acid. Moreover, some flavonoids, that is, rutin, cyanidin 3‐glucoside, and quercetin, occurred in almost all samples. This work provided a deepened characterization of bioactive compounds in SCG and can contribute to develop new strategies of reuses.